Recent analytical approaches to counterfeit drug detection - Abdulmumin A. Nuhu (Journal of Applied Pharmaceutical Science)
Counterfeiting of drugs has now become a lucrative multi-billion dollar business that threatens the effective delivery of health care services. Apart from Africa and other marginally developed parts of the world, the developed economies are equally not spared from the bane of this trade. To combat this menace, concerted efforts are needed from various facets of the community. In addition to visual inspections, sophisticated analytical tools are usually required in order to successfully distinguish counterfeits from the real stuffs. Attempt is made in this review to summarize the recent applications of these tools in keeping track with counterfeit drug flow. These are discussed under the headings of different approaches, including Near Infrared Spectroscopy, Raman Spectroscopy, Fluorescence and Phosphorescence measurements, Nuclear Magnetic Resonance imaging, X-ray and radio frequency analysis. In the quest to maintain their profit margin, the perpetrators of counterfeit pharmaceuticals will continue to develop ingenious ways to circumvent regulatory systems. Therefore, relentless efforts should continue to be deployed toward research and development in low cost, fast and efficient ways of detecting counterfeit drug at different stages of its existence.
Keywords: Counterfeit drugs, analytical tools, near infrared spectroscopy, nuclear magnetic resonance imaging, radio frequency analysis, detection